UiTM Law Newsletter (May - Aug 2019) - UiTM Shah Alam, Faculty of Law (Faculty of Law, 2019)
As we release our second e-newsletter, we continue to highlight and illustrate numerous programs and achievements occurring within UiTM Law. Our activities continue to broaden and deepen our reputation in response to the internationalisation of the education fraternity in Malaysia.